Usuários ou dependentes de drogas, dignidade da pessoa humana no âmbito dos juizados especiais criminais - Almeida, Jocy Gomes de (Universidade Federal do Tocantins, 2018)
This is a technical report linked to the line instruments of jurisdiction, access to justice and human rights, of the interdisciplinary professional Master's in the judicial and human rights of the Federal University of Tocantins (UFT) and school Superior of the judiciary of Tocantins (Asmat) with the objective of demonstrating the need to preserve the choices, the private life and the intimacy of users and drug addicts in the Special Criminal Court in the Dianópolis District of Tocantins State. The research carried out during the period from 2012 to 2016. The methodological course, aiming to improve the practice of judictional provision in Dianópolis District, was guided by quantitative research, since respondents are afraid of gossiping small cities. The drug user‟s submission of the justice system is stigmatizing, to the State, and does not meet the expectations of most experts who want the problem to be the responsibility of the health system. What is the alternative for problematic or non-problematic drug users who refuse to attend CAPS in small towns so that they do not fulfill the stereotype of criminals and patients, alleviating the stigma attached to them. Apply to drug users and dependents structuring measures compatible with legality. A legal alternative is to apply only the warning to marijuana users, considering the decriminalizing tendency that emerges from the suspended judgment of the Federal Supreme Court (RE 635659), in which the three votes collected, with some caveats, adopt this thesis. Treating the dependent as a criminal violates the super principle of the dignity of the human person. Prohibitionism has aggravated the situation of the dominated social classes, using medical arguments and moral panic to criminalize conduct, for purposes of social control. Law-makers are conservative in applying the law with harsh rigor, often assigning the crime of drug trafficking to low-cost users. It is also concluded the proposal for suggestions to the Court of Justice of the State of Tocantins as to the standardization of the detailed terms of occurrence, with the assistance of multidisciplinary teams for communications with the jurisdiction on the Criminal procedures and procedures for referrals to health services, uniformization of various procedures that assist, regulate and oportunizam the effective improvement of judicial attention to these users, and concludes with the proposal of the creation of rods with specific competence to act in the area of drugs the similarity of what happens with the rods related to the Crime of domestic violence.